Foreign experience in developing effective remuneration systems at construction enterprises - Dropa, Ihor (Ways to Improve Construction Efficiency, 2024)
The article explores international experience in developing effective wage systems with the aim of identifying key approaches and practices that can be adapted for construction enterprises in Ukraine. Various wage models applied in developed countries are analyzed, taking into account economic, social, and cultural factors. It is established that remuneration in the United States is characterized by individualized pay and bonus programs; in EU countries (such as Germany and Sweden) by tariff agreements and differentiated wages; in Japan by seniority-based bonuses and non-monetary incentives; and in China by collective responsibility. The key national models are considered with an emphasis on their advantages, implementation challenges, and potential for adaptation in Ukrainian enterprises. It is found that the most efficient foreign wage systems are based on a combination of fixed pay and flexible bonus mechanisms aimed at achieving both individual and collective goals. Modern approaches to compensation organization are reviewed, including KPI-based systems, pay-for-performance, base-up and teiki-shokyu mechanisms, performance-based remuneration, and the use of non-monetary incentives and social benefit packages. Special attention is paid to tariff grids, qualification grades, and the practice of collective bargaining in wage regulation. The feasibility of introducing hybrid wage systems in the Ukrainian construction sector is substantiated, as such models allow for consideration of project specifics, technological complexity, and personnel qualifications. The findings can be used to improve wage policies in construction enterprises to enhance employee motivation, reduce staff turnover, and build a stable human capital management system in the context of Ukraine’s post-war recovery..